2000
DOI: 10.1016/s1074-7613(00)00014-5
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for the dsRNA-Dependent Protein Kinase PKR in Innate Immunity to Viral Infection

Abstract: The double-stranded (ds) RNA-dependent protein kinase PKR is considered to play an important role in interferon's (IFN's) response to viral infection. Here, we demonstrate that mice lacking PKR are predisposed to lethal intranasal infection by the usually innocuous vesicular stomatitis virus, and also display increased susceptibility to influenza virus infection. Our data indicate that in normal cells, PKR primarily prevents virus replication by inhibiting the translation of viral mRNAs through phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
355
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(388 citation statements)
references
References 42 publications
21
355
2
Order By: Relevance
“…Of interest is that it is well documented that VSV replicates extremely efficiently in numerous types of tissue cultured cell-lines, possibly inferring that host defense mechanisms involving the IFNs in these cells are down regulated. 50 Our data further indicated that VSV could induce apoptosis very effectively in many tumorigenic cells, in vitro, including those cells defective in p53, myc and ras or overexpressing Bcl-2. 151,156 Importantly, VSV could also induce apoptosis of xenografted tumors in vivo, greatly reducing the growth of the tumor mass.…”
Section: Viruses As Oncolytic Apoptosis-inducing Agentssupporting
confidence: 69%
See 1 more Smart Citation
“…Of interest is that it is well documented that VSV replicates extremely efficiently in numerous types of tissue cultured cell-lines, possibly inferring that host defense mechanisms involving the IFNs in these cells are down regulated. 50 Our data further indicated that VSV could induce apoptosis very effectively in many tumorigenic cells, in vitro, including those cells defective in p53, myc and ras or overexpressing Bcl-2. 151,156 Importantly, VSV could also induce apoptosis of xenografted tumors in vivo, greatly reducing the growth of the tumor mass.…”
Section: Viruses As Oncolytic Apoptosis-inducing Agentssupporting
confidence: 69%
“…Such PKR7/7 animals were extremely sensitive to intra nasal infection with VSV and influenza virus and exhibited defective IFN-signaling in response to both virus and dsRNA. 50 Thus, along with members of the IRF family, PKR is likely an important mediator of dsRNA and virusinduced cell death.…”
Section: Interferon Regulation: Jaks and Statsmentioning
confidence: 99%
“…Active PKR has been shown to provoke release of NF-κB from its inhibitory subunit, IκB, by stimulation of the IKK kinase complex, thereby activating the NF-κB transcription factor and promoting the expression of multiple genes [57]. Finally PKR also induces cellular apoptosis, which serves as a natural process of preventing further viral infection [56,58].…”
Section: Unwanted Immune Responses Induced By Mrna Recognitionmentioning
confidence: 99%
“…PKR, an important effecter arm of the antiviral action against many viruses including EMCV, VSV, and HSV-1 [69][70][71], is a serine/threonine kinase and its mechanism of action is mediated through inhibition of translation initiation due to phosphorylation of EIF 2α. A detailed description of the PKR pathway is given in this issue by Meurs and Esteban.…”
Section: The Role Of Ifn-regulated Rnase L and Pkr In The Post-transcmentioning
confidence: 99%